2021
DOI: 10.1038/s41467-021-22392-w
|View full text |Cite
|
Sign up to set email alerts
|

A small climate-amplifying effect of climate-carbon cycle feedback

Abstract: The climate-carbon cycle feedback is one of the most important climate-amplifying feedbacks of the Earth system, and is quantified as a function of carbon-concentration feedback parameter (β) and carbon-climate feedback parameter (γ). However, the global climate-amplifying effect from this feedback loop (determined by the gain factor, g) has not been quantified from observations. Here we apply a Fourier analysis-based carbon cycle feedback framework to the reconstructed records from 1850 to 2017 and 1000 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 60 publications
4
20
0
Order By: Relevance
“…Previous studies quantified the magnitudes of these two feedbacks by assuming both feedbacks were linear and non-interactive (Arora et al, 2013;Friedlingstein et al, 2006). Interactions between the two feedbacks within the Earth system, which are defined as the nonlinear feedback in this study, have been largely ignored in most previous studies (Arora et al, 2013(Arora et al, , 2020Friedlingstein et al, 2006;Gregory et al, 2009;Plattner et al, 2008), an omission that has been challenged by several recent studies (Schwinger et al, 2014;Zhang et al, 2021;Zickfeld et al, 2011). For example, the interaction in the ocean can reduce the global ocean carbon uptake by 3.6% to 10.6% under a high CO 2 emission scenario (Schwinger et al, 2014) through its contribution of approximately −6% to the ocean carbon-concentration feedback, or approximately 60% to the ocean carbon-climate feedback (Zhang et al, 2021).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies quantified the magnitudes of these two feedbacks by assuming both feedbacks were linear and non-interactive (Arora et al, 2013;Friedlingstein et al, 2006). Interactions between the two feedbacks within the Earth system, which are defined as the nonlinear feedback in this study, have been largely ignored in most previous studies (Arora et al, 2013(Arora et al, , 2020Friedlingstein et al, 2006;Gregory et al, 2009;Plattner et al, 2008), an omission that has been challenged by several recent studies (Schwinger et al, 2014;Zhang et al, 2021;Zickfeld et al, 2011). For example, the interaction in the ocean can reduce the global ocean carbon uptake by 3.6% to 10.6% under a high CO 2 emission scenario (Schwinger et al, 2014) through its contribution of approximately −6% to the ocean carbon-concentration feedback, or approximately 60% to the ocean carbon-climate feedback (Zhang et al, 2021).…”
mentioning
confidence: 96%
“…could absorb CO 2 from warming-induced growing season extension and vegetation expansion that stimulates gross primary productivity, which is defined as the land carbon-climate feedback or the temperature sensitivity (Friedlingstein et al, 2003(Friedlingstein et al, , 2006. Modeling experiments showed that under rising CO 2 concentration scenarios, the carbon uptake response was largely dominated by the positive contribution from the carbon-concentration feedback (Arora et al, 2013(Arora et al, , 2020Gregory et al, 2009;Zhang et al, 2021), although the magnitudes of these two feedbacks varied with timescale and CO 2 emission scenario (Gregory et al, 2009;Zhang et al, 2021) and exhibited large uncertainties across different Earth system models (Arora et al, 2013(Arora et al, , 2020Friedlingstein et al, 2006Friedlingstein et al, , 2014Plattner et al, 2008) or terrestrial ecosystem models (Huntzinger et al, 2017;Liu et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Primary characteristics of the 11 models used in this study 2 is the change in the atmospheric CO 2 concentration and ΔT COU is the change in the surface atmospheric temperature over land at 4×CO 2 from the fully coupled simulation(Zhang et al, 2021).…”
mentioning
confidence: 99%